Chronic complications among patients with type 2 diabetes in Southern Ethiopia - Biniyam Demisse Andarge; Desta Haftu Hayelom; Sayih Mehari Degualem; Habtamu Esubalew Bezie; Habtamu Wondmagegn; Yohannes Habtegiorgis; Muluken Bekele Sorrie; Yilma Chisha (PLoS ONE, 2025)
Background Type 2 diabetes mellitus (T2DM) is a global health concern associated with complications that significantly impact patients’ quality of life and place significant burdens on healthcare systems. While the prevalence of T2DM is rising in Ethiopia, the scope and factors contributing to its complications remain understudied. Hence, this study aimed to assess the burden and identify associated factors of chronic complications among Type 2 diabetes mellitus patients attending Wolaita Sodo University Comprehensive Specialized Hospital in Southern Ethiopia. Methods A facility-based cross-sectional quantitative study was conducted from July 1 to August 30, 2024, involving 404 systematically sampled T2DM patients. Data on sociodemographic characteristics, clinical profiles, self-care practices, and chronic complications were collected through structured interviews and medical record reviews. Descriptive statistics summarized patient characteristics, while multivariable logistic regression identified factors associated with chronic complications. Results were reported as Adjusted Odds Ratios (AORs) with 95% Confidence Intervals (CIs), and a p-value < 0.05 was considered statistically significant. Results A total of 404 type 2 Diabetes mellitus patients participated in the study, with a response rate of 97.58%. The mean age of participants was 44.80 ± 14.10 years, 41.09% had diabetes for more than 5 years, and 64.85% had suboptimal glycemic control. Among participants, 45.54% (95% CI: 40.61–50.54) had at least one chronic complication, and one in five had multimorbidity. The most common microvascular complications were peripheral neuropathy (14.85%) and nephropathy (9.65%), while macrovascular complications included congestive heart failure (14.11%) and cerebrovascular disorders (11.39%). Multivariable logistic regression identified older age (AOR = 2.74; 95% CI: 1.73, 4.37; p < 0.000), female sex (AOR = 2.14; 95% CI: 1.12, 4.16; p = 0.039), longer diabetes duration (AOR = 2.98; 95% CI: 1.41, 6.54; p = 0.007), poor glycemic control (AOR = 2.02; 95% CI: 1.33, 3.09; p = 0.001), hypertriglyceridemia (AOR = 2.00; 95% CI: 1.06, 3.80; p = 0.038), high salt intake (AOR = 1.57; 95% CI: 1.06, 2.32; p = 0.024), and physical inactivity (AOR = 1.75; 95% CI: 1.16, 2.64; p = 0.008) as significant factors associated with chronic complications. Conclusion Nearly half of patients with Type 2 diabetes in Southern Ethiopia experienced chronic complications, emphasizing the need for improved prevention and management strategies. Strengthening diabetes care should include routine lipid and blood pressure screening, HbA1c testing where feasible, and nurse-led foot assessment. Community-based interventions promoting physical activity and dietary modification, along with patient education on glycemic control, should be scaled up. Implementing these feasible, low-cost measures within Ethiopia’s existing chronic care framework can help reduce the burden and improve health outcomes.